Influência de diferentes aditivos nucleantes na morfologia e nas propriedades do polipropileno moldado por injeção - Abreu, Andressa Argani (2018)
Samples of a polypropylene (PP) homopolymer were nucleated with three different nucleating agents: 1,3:2,4-bis (3,4-dimethylobenzylideno) sorbitol (DMDBS), bis(4-propylbenzylidene) propilsorbitol (propilsorbitol), and lithium 2,2-methylene-bis (4,6- di-tert-butylphenyl) phosphate (lithium organophosphate) at different concentrations. The influence of these additives on the PP morphology was studied by polarized light optical microscopy (PLOM) with hot stage, atomic force microscopy (AFM), differential scanning calorimetry (DSC) wide angle x-ray diffraction (WAXD), and small angle x-ray scattering (SAXS). The influence of these additives in flow induced crystallization was verified through rheological analysis, optical, mechanical and thermomechanical properties were also evaluated. An increase in lamella thickness and long period was verified in nucleated samples by SAXS, and rheological analysis revealed that pure PP is more sensitive to flow-induced orientation than nucleated samples. Microscopy analysis showed that the crystalline morphology of nucleated PP is formed by a fibrillar transcrystalline structure, which reduces the interaction of the crystalline phase with visible light, and the sample containing lithium organophosphate forms the structure with most refined fibrils. All nucleating agents, in every concentration evaluated, proved to be efficient regarding the beginning of crystallization, improving optical properties and enhancing the polymer stiffness. However, changes in the concentration of the additives DMDBS and propilsorbitol influenced some of the final properties of the samples, while the sample containing lithium organophosphate did not show variations, regardless of the additive content used. It can be said that lithium organophosphate provides a better cost-benefit than the other nucleating agents evaluated, once a smaller amount of additive is needed to achieve similar results